(3QbGHI GdeMceI GdOSJhQjI GdYdjG Ydi GdSdWI GdJbOjQjI dde`TQY (B/ s - (3jhSa YHOGdeMSf YHOGdaJGMs; (3eMeO HOQGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3JfGhdJ gPg GdOQGSI ehVhY QbGHI GdeMceI GdOSJhQjI GdYdjG Ydi GdSdWI GdJbOjQjI ddeTQY(B: (3aJfGhdJ eGgjI GdSdWI GdJbOjQjI ddeTQY h WHjYJgG h fWGb MOhOgG(B: (3h CgejI NVhYgG dQbGHI GdeMceI GdOSJhQjI GdYdjG(B: (3ceG JfGhdJ GdCSS GdJi GfWdbJ efgG GdeMceI GdOSJhQjI dQbGHI SdWI GdeTQY GdJbOjQjI(B: (3MjK JfGhdJ GdQbGHI Ydi eOi JMbjb GdeTQY debJVjGJ GdCef GdbGfhfi ai UhQg GdeNJdaI(B: (3h cPdc QbGHJgG Ydi GdNWC GdXGgQ ai JbOjQ GdeTQY(B: (3ceG JfGhdJ ehba GdeMceI ef GdQbGHI Ydi GdUhQ GdeNJdaI dYOe GdGNJUGU GdSdHi ddeTQY(B: (3h cPdc ehbagG ef eQGYGI GdVQhQGJ GdYedjI GdJi JMjW HYedjI GdJTQjY(B: (3ceG JYQVJ HfXQI fbOjI defgL GdeMceI ai GdQbGHI Ydi SdWI GdeTQY GdJbOjQjI JLGg HYV GdJWHjbGJ GdNGUI(B: (3Ke oNJeJ HJfGhd Cge GdVhGHW GdOSJhQjI GdJi CbQJgG GdeMceI h GSJXgQJgG gPg GdOQGSI HhUagG MOhkOG OSJhQjI jLH Ydi GdeTQY eQGYGJgG YfO JfXjeg ddMbhb GdOSJhQjI GdeNJdaI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2016s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B697-715s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdQbGHg Ydi GdSdWg GdJbOjQjg ddeTQYs; (3QbGHg GdeMceg GdOSJhQjg GdYdjG Ydi GdSdWg GdJbOjQjg ddeTQYs; (3QbGHg GdedGFeg s; (3eHOG GdGef GdbGfhfj s; (3GdQbGHg GdOSJhQjg Ydi GdNWG GdXGgQ s; (3eLGdGJ GdQbGHg GdOSJhQjg Ydi GdJfGSH aj GdeLGd GdJTQjYi s; (3UhQ YOe GdGNJUGU GdJTQjYi s; (3bQjfg GdOSJhQjg hGaJQGV UMg GdJTQjY s; (3GQcGf GdJTQjY s; (3MOhO SdWg GdeTQY GdJbOjQjg s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes